2020
DOI: 10.1007/s10549-020-05701-7
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and early stage breast cancer outcome: results from a prospective observational study

Abstract: Purpose Obesity and insulin resistance have been associated with poor prognosis in breast cancer (BC). The present prospective study aimed to investigate the impact of metabolic syndrome (MetS) and its components on early BC (eBC) patients' outcome. Methods MetS was defined by the presence of 3 to 5 of the following components: waist circumference > 88 cm, blood pressure ≥ 130/≥ 85 mmHg, serum levels of triglycerides ≥ 150 mg/dL, high density lipoprotein < 50 mg/dL and fasting glucose ≥ 110 mg/dL. Seven hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 43 publications
2
39
0
1
Order By: Relevance
“…Current evidence suggests that metabolic syndrome and its components are associated with an increased risk of breast cancer recurrence (3,168). A retrospective study conducted by Ewertz et al (29) assessed the events of locoregional recurrence and distant metastasis among 53,816 women with early-stage breast cancer up to 10 years after diagnosis and showed that obesity may have no effect on the risk of local recurrence (P > 0.05) but had a significant association with distant metastasis 5 to 10 years after diagnosis.…”
Section: Metabolic Syndrome and Prognosis Of Breast Cancer Recurrencementioning
confidence: 99%
See 3 more Smart Citations
“…Current evidence suggests that metabolic syndrome and its components are associated with an increased risk of breast cancer recurrence (3,168). A retrospective study conducted by Ewertz et al (29) assessed the events of locoregional recurrence and distant metastasis among 53,816 women with early-stage breast cancer up to 10 years after diagnosis and showed that obesity may have no effect on the risk of local recurrence (P > 0.05) but had a significant association with distant metastasis 5 to 10 years after diagnosis.…”
Section: Metabolic Syndrome and Prognosis Of Breast Cancer Recurrencementioning
confidence: 99%
“…Metabolic syndrome, also known as insulin resistance syndrome or syndrome X, is a type of multifactorial metabolic disease. The definition of MetS takes into account the presence of at least three factors, namely, abdominal obesity/high body mass index (BMI), insulin resistance, hypertension, hypertriglyceridemia, and low high-density lipoprotein (HDL) (3)(4)(5). The prevalence of obesity has increased rapidly in recent years with the number of overweight/obese people almost doubling since the 1980s, representing one-third of the world's population, and the proportion may reach 57.8 percent by 2030 (6,7).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6] HS is fundamental for the diagnosis of MAFLD, which also emerges in breast cancer patients, leading to adverse outcomes. [7,8] Female breast cancer has surpassed lung cancer as the most commonly diagnosed malignant tumor [9]. Great levels of obesity and physical inactivity, are closely correlated to BC and become a signi cant drive for the trends of growing BC prevalence.…”
Section: Introductionmentioning
confidence: 99%